Synergistic Doping for Pseudocapacitance Sites in Alkaline Carbon Supercapacitors. Issue 1 (23rd October 2017) - Ni, Mei; Huang, Zhenghong; Lian, Yimeng; Chen, Renjie; Zhang, Xiaoling; Nie, Hailiang; Yang, Wen
Abstract: Pseudocapacitance sites emanating from co‐doping with nitrogen and phosphorous in hiearchical carbon are identified by using near‐edge X‐ray absorption fine structure (NEXAFS) spectroscopy. Associated space charge capacitance, characterized by using ultraviolet photoelectron spectroscopy (UPS), is induced by charging and enhances interfacial capacitance. Electrodes with high mass loading (8 mg cm −2 ) provide high energy density, and high stability is obtained (91.4 % retention after 10, 000 cycles). We describe a two‐step synthetic procedure, relying on hard templating with nanosilica and pyrolyzing polyaniline in the presence of triphenylphosphine followed by silica etching and annealing in the presence of ammonia gas. This method yields hierarchical porous N−P co‐doped carbon (HP‐NPC). Abstract : Facial expression : Pseudocapacitance sites in alkaline carbon supercapacitors produced by doping are identified by using near‐edge X‐ray absorption fine structure spectroscopy. The generated higher density of states near the Fermi level is detected by using ultraviolet photoelectron spectroscopy, which can improve the interfacial capacitance.